Advantages and disadvantages of artificial intelligence in the foreign language English teaching-learning process - Mateo Ordóñez, Jonathan Andrés (2025)
Artificial intelligence and the integration of its technological tools in English language education offer an improvement in the development of English language skills. However, the perspectives of teachers and students remain unanalyzed. This study aims to explore the advantages and disadvantages of integrating artificial intelligence into the foreign language (English) teaching-learning process, considering the perspectives of both teachers and students using AI tools in English teaching-learning practices. The study involved a sample of English teachers and thirteenth-grade students and used qualitative research methods such as one-to-one interviews. By analyzing the perspectives of both English teachers and students, the study results highlighted that artificial intelligence offers multiple benefits to enhance the English language teaching-learning development such as personalized learning, time-saving, and support for teachers in administrative tasks. In addition, the study also focuses on the disadvantages that AI tools include, affecting the English language teaching-learning development such as lack of teacher-student interaction and students' dependence on artificial intelligence. The results of this research will contribute to existing literature on technology in English language education and provide valuable information for educators and curriculum developers looking to take advantage of artificial intelligence to enhance the English language teaching-learning process.